Boost efficiency performance through the enhancement of duty cycle based MPPT algorithm - Badawi, Ahmed; Elzein, I. M.; Alqaisi, Walid; Zyoud, Al Hareth (International Journal of Applied Power Engineering (IJAPE), 2025)
The use of direct power control (DPC) has become popular as an effective control strategy for pulse width modulated (PWM) converters. The incremental conductance algorithm (INC) is utilized to control the duty cycle (D) in tracking the optimal point to increase power efficiency in wind energy conversion systems (WECS). WECS parameters are adjusted to achieve unity power factor, allowing the system to extract maximum power (????) from WECS. Simulation results show that wind speed has a significant impact on the captured power, with a proportional relationship between wind speed and power. Control strategies are employed to optimize the (D) to reach the desired operating point. A DC-DC boost converter is connected to WECS, where the (D) controls the MOSFET to maintain ???? at the optimal level on the DC link. Various wind speed profiles are simulated in this study to evaluate system efficiency, especially under conditions of rapid wind speed fluctuations. The controller based on (D) demonstrates superior tracking performance through the DC link, ensuring that ???? remains at an optimal level.